The Analysis of PT. Krakatau Steel (Persero) Tbk’s Business Transformation Strategy Towards A Sustainable Company - Antonius Alijoyo; Hidayatudin Shodikin (Journal of Social Science, 2022)
The objective of the study was analyzing the Business Transformation Strategy of PT. Krakatau Steel (Persero) Tbk Towards a Sustainable Company. The research followed a qualitative descriptive method. The results of the analysis show that the business transformation strategy carried out by PT. Krakatau Steel (Persero) Tbk towards a sustainable firm is done through debt restructuring and cost efficiency to increase labor productivity to lead the company to profitability. As a business entity that grows and develops in the community, this company also always strives to maintain harmonious relations with the surrounding community through corporate social responsibility (CSR) or partnerships and the Community Development Program (PKBL), which is held regularly every year. In addition, PT. Krakatau Steel (Persero) Tbk also consistently takes part in the Company Performance Assessment (PROPER) program conducted by the Republic of Indonesia's Ministry of Environment and Forestry.